Domestic arrangements : a novel - Klein, Norma, 1938- (M. Evans, 1981)
An unusual New York family deals with their 14-year-old daughter's success as a nymphet film actress and with her first affair, their 16-year-old daughter's wish to have one, and the breakup of the parent's marriage.